Colicins U and Y inhibit growth of Escherichia coli strains via recognition of conserved OmpA extracellular loop 1 - Bosák, Juraj; Micenková, Lenka; Doležalová, Magda; Šmajs, David (International journal of medical microbiology, 2016)
Interactions of colicins U and Y with the OmpA (Outer membrane protein A) receptor molecule were studied using site-directed mutagenesis and colicin binding assay. A systematic mutagenesis of the colicin-susceptible OmpA sequence from Escherichia coli (OmpAEC) to the colicin-resistant OmpA sequence from Serratia marcescens (OmpASM) was performed in regions corresponding to extracellular OmpA loops 1-4. Susceptibility to colicins U and Y was significantly affected by the OmpA mutation in loop 1. As with functional analysis, a decrease in binding capacity of His-tagged colicin U was found for recombinant OmpA with a mutated segment in loop 1 compared to control OmpAEC. To verify the importance of the identified amino acid residues in OmpA loop 1, we introduced loop 1 from OmpAEC into OmpASM, which resulted in the substantial increase of susceptibility to colicins U and Y. In addition, colicins U and Y were tested against a panel of 118 bacteriocin non-producing strains of four Escherichia species, including E. coli (39 strains), E. fergusonii (10 strains), E. hermannii (42 strains), and E. vulneris (27 strains). A majority (82%) of E. coli strains was susceptible to colicins U and Y. Interestingly, colicins U and Y also inhibited all of the 30 tested multidrug-resistant E. coli O25b-ST131 isolates. These findings, together with the fact that OmpA loop 1 is important for bacterial virulence and is evolutionary conserved, offer the potential of using colicins U and Y as specific anti-OmpA loop 1 directed antibacterial proteins.
Keywords: Microbial Sensitivity Tests; Colicin U; Humans; mutační analýza DNA; Protein Binding; koliciny; Female; mikrobiální testy citlivosti; Colicin Y; OmpA; Escherichia coli; Serratia marcescens; lidé; Bacterial Outer Membrane Proteins; Colicins; DNA Mutational Analysis; proteiny vnější bakteriální membrány; ženské pohlaví; Male; Colicin-receptor interaction; vazba proteinů; mužské pohlaví